Polymeric carbon encapsulated Si nanoparticles from waste Si as a battery anode with enhanced electrochemical properties. (1st June 2019) - Gan, Chuanhai; Zhang, Chengkun; Liu, Pengfei; Liu, Yingkuan; Wen, Weidong; Liu, Bang; Xie, Qingshui; Huang, Liuqing; Luo, Xuetao
Abstract: A facile method is proposed to prepare Si nanoparticles encapsulated in polymeric carbon (SiNPs-PC) as anode materials for lithium ion batteries. Si nanoparticles (SiNPs) with average diameter of 125 nm are prepared. Under the aid of silane coupling agent, SiNPs are coated with phenolic resin, and SiNPs-PC composite is prepared after carbonization engineering. The SiNPs-PC anode with 63.7 wt% of Si exhibits greatly strengthened electronic conductivity and relatively stable electrode interface. The SiNPs-PC anode delivers a reversible capacity of 984 mA h g −1 with 84% capacity retention after 100 cycles at a current density of 0.1 A g −1 and 710 mA h g −1 after 800 cycles at a current density of 1 A g −1 . When cycled at a very larger current density of 10 A g −1, a decent reversible capacity of 404 mA h g −1 can be harvested, which is still higher than the theoretical capacity of commercial graphite anode. The electrochemical performances are systematically discussed on microstructure and morphology of electrode materials. The feedstock of SiNPs is recycled from waste Si, and the preparation of SiNPs-PC composite is facile, cost-effective and environmentally benign, which shows great potential of industrial production.